Adsorption affinity and selectivity of 3-ureidopropyltriethoxysilane grafted oil palm empty fruit bunches towards mercury ions - Kunjirama, M. (Springer Verlag, 2017)
This study was conducted to investigate the potential application of oil palm empty fruit branches (OPEFB) as adsorbents to remove organic methylmercurry, MeHg(II), and inorganic Hg(II) from aqueous solution. The OPEFB was functionalized with amine containing ligand namely 3-ureidopropyltriethoxysilane (UPTES) aiming for better adsorption performance towards both mercury ions. The adsorption was found to be dependent on initial pH, initial concentraton, temperatures, and contact time. The maximum adsorption capacities (Qm.exp) of Hg(II) adsorption onto OPEFB and UPTES-OPEFB were 0.226 and 0.773 mmol/g, respectively. The Qm.exp of MeHg(II) onto OPEFB, however, was higher than UPTES-OPEFB. The adsorption kinetic data obeyed the Elovich model and the adsorption was controlled by the film-diffusion step. The calculated thermodynamic parameters indicate an endothermic adsorption process. Adsorption data analysis indicates that the adsorption mechanism may include ion-exchange, complexation, and physisorption interactions. The potential applications of adsorbents were demonstrated using oilfield produced water and natural gas condensate. The UPTES-OPEFB offered higher selectivity towards both mercury ions than OPEFB. The regenerability studies indicated that the adsorbent could be reused for multiple cycles. © 2017, Springer-Verlag Berlin Heidelberg.